Implementation of Jigsaw in Civics Subject at MIN 10 Southeast Aceh - Zaid, Muhammad Idris Maas; Adlani, Nazri; Rahman, Abdul (Yayasan Zia Salsabila, 2025)
This study aims to determine the effectiveness of the Jigsaw learning model in improving student learning outcomes in Civics (PKn) at MIN 10 Southeast Aceh. Civics learning is often considered boring by students because it tends to be theoretical and one-way. To overcome this, the Jigsaw cooperative learning model is implemented, which emphasizes group collaboration and individual responsibility. This study uses a quantitative approach with a quasi-experimental design. Data were obtained through pretests and posttests given to students before and after the model was implemented. The results showed a significant increase in student learning outcomes after the Jigsaw model was implemented. These findings indicate that the model can be an effective alternative learning strategy to improve conceptual understanding and student engagement in Civics learning.